2021
DOI: 10.1177/0018720821990484
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Temporal Variation and Individual Differences in Driver Cognitive Workload on ECG-Based Detection

Abstract: Objective This paper aimed to investigate the robustness of driver cognitive workload detection based on electrocardiogram (ECG) when considering temporal variation and individual differences in cognitive workload. Background Cognitive workload is a critical component to be monitored for error prevention in human–machine systems. It may fluctuate instantaneously over time even in the same tasks and differ across individuals. Method A driving simulation study was conducted to classify driver cognitive workload … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A study conducted by Yang et al [29] explored the robustness of detecting driver cognitive workload using ECG, while considering changes over time and individual variations in cognitive workload. They conducted a driving simulation experiment to categorize driver cognitive workload across four experimental scenarios (baseline, N-back task, texting, and N-back task with texting distraction).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Yang et al [29] explored the robustness of detecting driver cognitive workload using ECG, while considering changes over time and individual variations in cognitive workload. They conducted a driving simulation experiment to categorize driver cognitive workload across four experimental scenarios (baseline, N-back task, texting, and N-back task with texting distraction).…”
Section: Resultsmentioning
confidence: 99%
“…It also found that ECG are usually gathered in relatively short driving experiment, typically less than one hour for cognitive load detection. The reliability of cognitive load detection might be decreased in prolonged driving if the algorithms used are trained solely with early-stage driving data [29]. This is due to temporal variations in the cognitive load.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies could extend our study to include a more diverse population (e.g., including individuals with both genders and with diverse driving experience) in order to consider the potential impact of gender and driving experience on the experimental results. Finally, the measures used in this experiment represent average values over a certain period, without considering temporal changes in MWL [32]. Thus, future research could explore the temporal characteristics of MWL and examine how MWL would change over time.…”
Section: Limitationsmentioning
confidence: 99%
“…In simulated driving environments, gaze fixation duration decreases with an increase in task load [31]. Heart rate and heart rate variability are also commonly used and are effective ECG measures for assessing drivers' MWL [32]. Skin conductance level (SCL) and skin conductance response (SCR) are frequently used in electrodermal activity measurements to assess MWL.…”
Section: Introductionmentioning
confidence: 99%
“…pressure could be exploited with blood pressure cuff applied to the upper arm and connected to monitor [82,83]. And "posture" involving head, face, hand and body features is mainly recorded by camera [84].…”
Section: Plos Onementioning
confidence: 99%